Developing a structural equation model: Case study of Thai port developing - Settadalee, Ronnakrit; Muangpan, Thanyaphat (Interdisciplinary Research Review, 2022)
The Covid-19 pandemic substantially affects the global tourism industry. The cruise travel business has been one of the most important sources of national income. Therefore, the first need is to improve the cruise ports. This research aims to analyse and develop the structural model of the relationships, dimensions as well as indicators of the cruise port development. The survey research is used in data collection with 342 samples from the Thai tourism business association as well as from the cruise and yacht professionals' association. Three hypotheses drive the indicators to set a relationship among three dimensions that include the cruise tourism factor, the cruise ship characteristics, and the cruise port dimension. Structural equation modelling (SEM) was used to develop this model using the PLS method. The findings revealed that the development of the Thai cruise port model offers the relationship of three dimensions and sixty-nine indicators for improving Thai cruise ports. These results showed a path analysis and measurement model confirming the indicators among these dimensions. The results were also conceptualized into a guideline for how to implement a policy for the cruise port development to support the tourism industry and national economics.